Literature Review: Community Empowerment in Prevention and Control of Dengue Hemorrhagic Fever - Putri, Alifia Adfriska Puspita; Martini, Martini; Hestiningsih, Retno (Jurnal Ilmiah Mahasiswa, 2021)
The incidence of Dengue Hemorrhagic Fever (DHF) in Indonesia is still fluctuating, indicating that the handling carried out in the community is still running optimally. Several studies have shown that community empowerment is able to increase community knowlendge and community awarness by using targeted implementation. The purpose of this study was to determine the form of community empowerment in the prevention and control of DHF. The method used in this research is literature review study. Libraries are made online through several website or internet sites such as MEDLINE, ScienDirect, Garuda, and Google Scholar. This research was conducted on 21 articles consisting of 15 national articles and 6 international articles. The result of this research is increasing public knowledge about the problem of DHF.